Analysis of Safety Concerns on Herbal Products with Assumed Phytoestrogenic Activity - A. Marije Tjeerdsma; Florence P. A. M. van Hunsel; Sonja van de Koppel; Corine Ekhart; Annabella Vitalone; Herman J. Woerdenbag (MDPI AG, 2023)
Phytoestrogens (PEs) are plant-based compounds that can interact with estrogen receptors and are mainly used to treat menopausal complaints. However, the safety of products with assumed phytoestrogenic activity is not fully understood. This study aimed to identify plant species with assumed phytoestrogenic activity, review existing literature on their use and safety, and critically evaluate adverse reaction (AR) reports of single-herb, multi-herb, and mixed-multiple products, as submitted to the Netherlands Pharmacovigilance Centre Lareb and to VigiBase of the World Health Organization (WHO). In the Lareb database, the most commonly reported plant species to cause ARs (total of 67 reports) were Actaea racemosa L. (black cohosh) (47.8%), Humulus lupulus L. (hops) (32.8%), and Glycine max (L.) Merr. (soybean) (22.4%). In the VigiBase database (total of 21,944 reports), the top three consisted of Glycine max (L.) Merr. (71.4%), Actaea racemosa L. (11.6%), and Vitex agnus-castus L. (chaste tree) (6.4%). In the scoping review (total of 73 articles), Actaea racemosa L. (30.1%), Glycine max (L.) Merr. (28.8%), and Trifolium pratense L. (13.7%) were the most frequently mentioned plant species. ARs were most frequently reported in the system organ classes "gastrointestinal disorders", "skin and subcutaneous tissue disorders", "reproductive system and breast disorders", and "general disorders and administration site conditions". Furthermore, from the scoping review, it appeared that the use of products with assumed phytoestrogenic activity was associated with postmenopausal bleeding. It was concluded that, while the potential benefits of products with assumed phytoestrogenic activity have been extensively pursued, the potential occurrence of ARs after using these products is less well understood. This study highlights the need for further investigation and careful monitoring of these products to better understand their effects and ensure the safety and well-being of individuals using them.